Renal infarction due to lupus vasculopathy. (August 2015) - Varalaxmi, B; Sandeep, P; Sridhar, A V S S N; Raveendra, P; Kishore, C Krishna; Ram, R; Kumar, V Siva
In the ISN/RPS 2003 classification of lupus nephritis (LN) renal vascular lesions are not mentioned. We present a patient with postpartum lupus vasculopathy. The renal biopsy in our patient showed concentric intimal thickening with narrowed lumen. No inflammatory changes were found. It also revealed immunoglobulin and complement deposition on the wall of the arteriole. These changes indicate lupus vasculopathy. The glomeruli revealed diffuse proliferative glomerulonephritis, with wire loops and cellular crescent in one glomerulus. The patient showed improvement with immunosuppression.